PEMBELAJARAN IPA DENGAN PRAKTIKUM BERBASIS KONTEKS DAN LITERASI SAINS: PERSPEKTIF GURU SD DI SUKABUMI - Windyariani, Sistiana (Jurnal Pendidikan Matematika dan IPA, 2017)
Laboratory activities are important of science learning at any level. At the elementary school lab work needs to be done in the context of daily life in order to training scientific literacy. This study aims to determine how the teacher's perspective on science teaching in primary schools in Sukabumi, West Java in the academic year 2015/2016. Research methods such as survey, data analysis quantitatively and qualitatively. Data collection used is a kuosioner sheet and interview guides to explore the teacher's perspective grade 4 and 5 primary school in implementing and understanding the context-based practicum. The results showed all the teachers (100%) stated the laboratory activities is important to be implemented, but most of the teachers (75%) stated the laboratory activities difficult to implemented. Teachers argued do not understand the practicum as an activity that can be done simply based on the context of everyday life in an effort to train science literacy (97%). The results of the elementary teacher's perspective is able to provide precise information about the condition of learning science as a material improvement regarding practical learning becomes more meaningful. Keywords: practical laboratory, context, Scientific Literacy